1976
DOI: 10.1111/j.1834-7819.1976.tb01047.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental survey of students at the Australian National University —1972

Abstract: A sample of 422 students at the Australian National University was examined in 1972. Results for the 302 full-time student sample were considered significant and are presented in this report. The students were found to have a relatively low (for Australia) DMFT of 13.8, Oral Hygiene Index of 0.9 and Periodontal Index of 0.75. Seventy-two percent of students had attended a dentist within the previous year and F/DMFT ratio was 76 percent. Estimates of time and costs of treatment needs are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…During the last 30 yr, rnany studies have been conducted into students' dental health, but most of them have not included PTGs for all subjects (9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…During the last 30 yr, rnany studies have been conducted into students' dental health, but most of them have not included PTGs for all subjects (9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Results of this study have shown that mean of gingivitis values decrease with advancing class level, this is due to the fact that dental school students possess a higher standard of awareness about their dental health and reflect the wide availability of dental services among them (10,11) . It is also due to the motivation regarding the importance of prevention oral diseases among finish dental students; this is in agreement with many authors (12,13,14) .…”
Section: Discussionmentioning
confidence: 87%